High mean platelet volume after myocardial infarction: is it due to consumption of small platelets?. Issue 6458 (8th December 1984) - Sewell, R; Ibbotson, R M; Phillips, R; Carson, P
Abstract : Seventy nine men surviving after sustaining a myocardial infarction in 1982, and who had at that time had raised mean platelet volumes compared with controls, were followed up after 18 months. The shape of each man's platelet distribution curve was calculated from the mean platelet volume, platelet count, and platelet distribution width. The calculated curves were in close agreement with the curves plotted by the Coulter counter from the raw data. These curves did not differ significantly from those of a current control group, but the curves plotted from the variables measured at the time of myocardial infarction in 1982 showed a deficit of platelets in the volume range 5-12 fl amounting at maximum to 30% (p less than 0.0001); there were no significant differences above 12 fl. The deficit of small platelets became more appreciable during initial admission, was less at one month's follow up, and had disappeared at one year. The deficit of small platelets is probably an effect rather than a cause of infarction.